MSME Development Strategy in Tourism Destination Tanjung Lesung, Tanjung Jaya Village,District Panimbang, Pandenglang - Goenadhi, Felix; Santoso, Adhi Setyo (Journal of The Community Development in Asia, 2023)
Tanjung Jaya Village as one of the villages in Panimbang Regency provides a number of very high business potentials. promising. However, this business opportunity has not been fully utilized by the people of Tanjung Jaya and MSME actors. Therefore, this program aims to develop strategies regarding human resources, marketing, bookkeeping, and MSME products in a professional and independent manner to support income and improve the welfare of the people in Tanjung Jaya Village. The implementation method used is interviews, and seminars for MSME actors. First of all, the researcher asked MSME actors in Tanjung Jaya Village about the concept of managing a business professionally, innovatively, creatively and independently. Next, researchers will score and triangulate the results of interviews with the Tanjung Jaya community to carry out MSME development strategies. With the implementation of these activities, it has a positive impact on the people of Tanjung Jaya Village to increase business potential, especially in the MSME sector. In the end, this program can support income and improve the welfare of the people of Tanjung Jaya Village and also contribute to increasing economic growth in Panimbang Regency.